GABAA/Benzodiazepine Receptor Complex in the Dorsal Hippocampus Mediates the Effects of Chrysin on Anxiety-Like Behaviour in Female Rats - Rodríguez-Landa, Juan Francisco; Hernández-López, Fabiola; Martínez-Mota, Lucía; Scuteri, Damiana; Bernal-Morales, Blandina; Rivadeneyra-Domínguez, Eduardo (Frontiers in Behavioral Neuroscience, 2022)
Systemic injections of the flavonoid chrysin (5,7-dihydroxyflavone) exert anxiolytic-like effects in ovariectomised and cycling female rats through actions on gamma-aminobutyric acid-A (GABAA) receptors; however, it is unknown if chrysin directly acts on brain structures that are involved in regulating emotional processes, such as the hippocampus. The present study evaluated the effects of intrahippocampal microinjections of 0.25, 0.5 and 1 μg of chrysin on anxiety-like behaviour in the elevated plus maze and locomotor activity test in female rats in proestrus and dioestrus. Similar doses of the neurosteroid allopregnanolone were used as a reference GABAergic anxiolytic drug. The participation of the GABAA/benzodiazepine receptor complex was evaluated by administering the antagonists picrotoxin, bicuculline and flumazenil. In proestrus, 0.5 μg and 1 μg of chrysin and allopregnanolone induced anxiogenic-like behaviour. In dioestrus, chrysin and allopregnanolone (0.5 μg ) induced anxiolytic-like effects. Picrotoxin, bicuculline and flumazenil prevented the effects of chrysin and allopregnanolone in both proestrus and dioestrus. None of the treatments significantly affected locomotor activity. These results indicate that the GABAA/benzodiazepine receptor complex in the dorsal hippocampus regulates the effects of chrysin on anxiety-like behaviour, similar to the actions of allopregnanolone. The divergent effects of treatments across the oestrous cycle phases suggest complex interactions between GABAA receptors and compounds with an anxiolytic potential.